STRATEGI PEMERINTAH DALAM PENGEMBANGAN WISATA HUTAN MANGROVE (Studi di Kampung Pomako, Kecamatan Mimikka Timur, Kabupaten Mimika, Provinsi Papua Tengah) - Mitapo, Sipriana (CV. ULIL ALBAB CORP, 2025)
The problem with mangrove forest tourism is the unorganized nature of this tourist area and the lack of community participation in its development. Therefore, government intervention is needed to develop mangrove forest tourism. This study aims to determine the government's strategy for developing mangrove forest tourism in Pamoka Village, East Mimika District, Mimika Regency. The research used qualitative descriptive research, using observation, interviews, and documentation as data collection techniques. Data analysis utilized data reduction, data presentation, and conclusions. The results show that the mangrove forest tourism development strategy in Pomako Village is implemented through distributive, regulatory, and constituent strategies. Supporting strategies for mangrove forest tourism development include promoting mangrove forest tourism, developing sustainable tourism, maintaining and preserving the natural potential of the mangrove forest in ecotourism areas, introducing local customs as supporting tourist attractions for mangrove ecotourism, and utilizing ecotourism potential as a business opportunity to optimize the economy.